DOCUMENTING THE CATALOGING PRACTICES AND POLICIES AMONG SELECTED LIBRARIES IN KAZAKHSTAN - MANABAT, April R. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2021)
Objective. A survey was conducted among selected librarian catalogers in Kazakhstan to determine the current cataloging practices and policies being employed in their respective libraries. Methods. Responses suggested that cataloging is still one of the important aspects of the library work even with the emergence of electronic resources. Results. While many were still applying traditional standards such as MARC, AACR, LC and DDC in their descriptive cataloging and authority works, catalogers were interested in new standards such as RDA and BIBFRAME. Conclusions. Finally, interests in having a unified online catalog as well as more trainings on the field of cataloging and metadata librarianship in the future has also been considered by these libraries to improve the quality of their cataloging work.